The balanced microenvironment regulated by the degradants of appropriate PLGA scaffolds and chitosan conduit promotes peripheral nerve regeneration - Panjian Lu; Gang Wang; Tianmei Qian; Xiaodong Cai; Ping Zhang; Meiyuan Li; Yinying Shen; Chengbin Xue; Hongkui Wang (Materials Today Bio, 2021)
Tissue-engineered nerve grafts (TENGs) are the most promising way for repairing long-distance peripheral nerve defects. Chitosan and poly (lactic-co-glycolic acid) (PLGA) scaffolds are considered as the promising materials in the pharmaceutical and biomedical fields especially in the field of tissue engineering. To further clarify the effects of a chitosan conduit inserted with various quantity of poly (lactic-co-glycolic acid) (PLGA) scaffolds, and their degrades on the peripheral nerve regeneration, the chitosan nerve conduit inserted with different amounts of PLGA scaffolds were used to repair rat sciatic nerve defects. The peripheral nerve regeneration at the different time points was dynamically and comprehensively evaluated. Moreover, the influence of different amounts of PLGA scaffolds on the regeneration microenvironment including inflammatory response and cell state were also revealed. The modest abundance of PLGA is more instrumental to the success of nerve regeneration, which is demonstrated in terms of the structure of the regenerated nerve, reinnervation of the target muscle, nerve impulse conduction, and overall function. The PLGA scaffolds aid the migration and maturation of Schwann cells. Furthermore, the PLGA and chitosan degradation products in a correct ratio neutralize, reducing the inflammatory response and enhancing the regeneration microenvironment. The balanced microenvironment regulated by the degradants of appropriate PLGA scaffolds and chitosan conduit promotes peripheral nerve regeneration. The findings represent a further step towards programming TENGs construction, applying polyester materials in regenerative medicine, and understanding the neural regeneration microenvironment.